Pea–cucumber crop rotation suppresses Fusarium pathogens by reshaping soil microbial communities and enhancing nutrient availability - Xu, Jun; Yao, Yuan; Pan, Liu; Zhang, Ningyuan; Li, Donghao; Chen, Xuehao (Frontiers in Microbiology, 2025)
IntroductionPea–cucumber rotation combined with straw return as green manure is an environmentally friendly management strategy to suppress cucumber (Cucumis sativus L.) Fusarium wilt (FW) and alleviate continuous cropping obstacles.MethodsWe evaluated the variations in soil microbial compositions and nutrient levels between long-term cucumber monocropping and pea–cucumber rotation patterns via metagenomic sequencing and determination of soil properties.ResultsThe study found that the bacterial communities exhibited marked diversity, whereas the α-diversity of fungal communities was significantly reduced. Based on the relative abundance of differential fungi and bacteria at the genus level, the genus Bacillus showed the highest abundance, with a two-fold increase, whereas Fusarium species exhibited a 4.9-fold reduction following the pea–cucumber rotation. Additionally, the contents of available nitrogen, potassium, and phosphorus in the soil increased by more than 1.3-fold after the rotation. Correlation analysis revealed that the genus Bacillus and available potassium were significantly and negatively correlated with Fusarium pathogens. Notably, the isolated B. pumilus and B. safensis strains significantly suppressed the growth of cucumber FW pathogens.DiscussionThese findings provide valuable insights for optimizing the combination of soil Bacillus populations and nutrient availability to maintain soil ecosystem health and improve cucumber growth and yield.